(untitled) (Al-Academy, 2016)
The super good artist, and its leading role experience detailed instrumental in the birth of the modern Iraqi drawing because of the represented technical personal super good in leading production Iraqi drawing since the early forties. If taken Excellence professional to experience the artist compared to the experiences of other pioneers and strengthened, the stylistic diversity through metaphors Different presented by the super good so that covered the period from romantic to Impressionism through schools drawing expressionism and cubism space, and therefore the heritage and the richness of diversity stylistic high to experience the good represents documentation required by contemporary Iraqi formation history, so the researcher found the need to study metaphors in super good artist and documented experience